ADAR1 haploinsufficiency and sustained picornaviral RdRp dsRNA synthesis synergize to dysregulate RNA editing and cause multi-system interferonopathy - Caitlin M. Miller; James H. Morrison; Laura Bankers; Rachael Dran; Julia M. Kendrick; Emma Briggs; Virginia L. Ferguson; Eric M. Poeschla (mBio)
ABSTRACT Sensing of viral double-stranded RNA (dsRNA) by MDA5 triggers abundant but transient interferon-stimulated gene (ISGs) expression. If dsRNA synthesis is made persistent by transgenically expressing a picornaviral RNA-dependent RNA polymerase (RdRp) in mice, lifelong MDA5-MAVS pathway activation and marked, global ISG upregulation result. This confers robust protection from viral diseases, but in contrast to numerous other chronic MDA5 hyperactivation states, the mice suffer no autoimmune or other health consequences. Here, we find that they further confound expectations by being resistant to a strong autoimmunity (lupus) provocation. However, knockout of one allele of Adar breaks the autoinflammation-protected state of RdRptg mice and results in a severe disease that resembles interferonopathies caused by MDA5 gain-of-function protein mutations. Adar+/– mice are healthy, but Adar+/– RdRptg mice have shortened lifespan, stunted growth, premature fur graying, poorly developed teeth, skeletal abnormalities, and extreme ISG elevations. A-to-I edits are both abnormally distributed and increased (numbers of genes and sites). These results, with a nucleic acid-triggered and MDA5-wild-type model, illuminate the ADAR1-MDA5 axis in the regulation of innate immunity and establish that viral polymerase-sourced dsRNA can drive autoinflammatory disease pathogenesis.IMPORTANCERNA virus double-stranded RNAs (dsRNAs) are important pathogen-associated molecular patterns that are sensed by the RIG-I-like receptor MDA5, which triggers an acute innate immune response involving many interferon-stimulated genes (ISGs). One key to a healthy innate immune system is that MDA5 does not sense endogenous dsRNA. This is normally ensured by dsRNA duplex-disrupting ADAR1 editing of host dsRNAs. Picornavirus RdRptg mice have an unusual constitutive MDA5 activation state, with very high lifelong MDA5-mediated ISG expression that confers robust protection from diverse lethal viruses. Importantly, and in contrast to numerous other chronic MDA5 hyperactivation states, the mice develop no autoinflammatory consequences. If we delete one ADAR1 allele, however, which by itself is well tolerated, the mice develop a multisystem disease that resembles the human interferonopathy Singleton-Merten syndrome. In contrast to other MDA5/ADAR1 disease models, the MDA5 and ADAR1 proteins are both wild type in this dsRNA-driven model.